2021
DOI: 10.3389/fcell.2021.640094
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics and VMP1-Related Selective Mitophagy in Experimental Acute Pancreatitis

Abstract: Mitophagy and zymophagy are selective autophagy pathways early induced in acute pancreatitis that may explain the mild, auto limited, and more frequent clinical presentation of this disease. Adequate mitochondrial bioenergetics is necessary for cellular restoration mechanisms that are triggered during the mild disease. However, mitochondria and zymogen contents are direct targets of damage in acute pancreatitis. Cellular survival depends on the recovering possibility of mitochondrial function and efficient cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…2C). Interestingly, upregulation of gene expression in this pathway suggest that VMP1 KO cells may be more sensitive to exposed cytoplasmic mtDNA which may be increased in VMP1 KO cells, consistent with previous reports demonstrating that VMP1 mediates the selective degradation of damaged mitochondria by mitophagy [29]. We also observed changes in gene expression in genes associated with calcium signaling, including a downregulation of SERCA and upregulation of other genes associated with calcium signaling in VMP1 KO cells (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2C). Interestingly, upregulation of gene expression in this pathway suggest that VMP1 KO cells may be more sensitive to exposed cytoplasmic mtDNA which may be increased in VMP1 KO cells, consistent with previous reports demonstrating that VMP1 mediates the selective degradation of damaged mitochondria by mitophagy [29]. We also observed changes in gene expression in genes associated with calcium signaling, including a downregulation of SERCA and upregulation of other genes associated with calcium signaling in VMP1 KO cells (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Typically, with NLRP3 activation, p62 is recruited to damaged mitochondria which are then ubiquitinated through a Parkin-mediated mechanism for degradation, but mitophagy is defective in the absence of VMP1 expression which causes an accumulation of damaged mitochondria [51,52]. Additionally, another mechanism that restricts in ammasome activation involves the interaction between p62 and ASC which targets in ammasome components to autophagosomes for degradation although this response is likely defective in VMP1 KO cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the number of active mitochondria was lesser in VMP1 KO cells compared to WT cells despite a significant increase in the overall number of mitochondria (Fig 4A). The observation implied an accumulation of dysfunctional mitochondria in VMP1 KO cells, which is consistent with a recent report, demonstrating that VMP1 is also required to recycle malfunctional mitochondria through mitophagy [40]. In alignment with the lower levels of active mitochondria observed in VMP1 KO cells, we parallelly detected a marked reduction of basal cellular respiration in these KO cells (S4A and S4B Fig) . Since FA treatment failed to rescue DENV infection in VMP1 KO cells, we decided to test whether this was due to impaired beta-oxidation capacity.…”
Section: Tmem41b and Vmp1 Deficiencies Compromise Mitochondrial Betao...supporting
confidence: 92%
“…32,33 Drp1 is often upregulated during mitochondrial fission, whereas MFN1 is downregulated during that process. 34,35 Yang et al 36 found that the squamosamide derivative FLZ could inhibit mitochondrial fission via downregulation of Drp1; Liu et al 37 reported that HMGB1 could inhibit mitochondrial fission in lung cancer cells via mediation of Drp1 and MFN1. Our findings were in line with those previous reports, by suggesting that Puerarin could reverse LPS-induced mitochondrial fission in H9C2 cells by regulating Drp1 and MFN1.…”
Section: Discussionmentioning
confidence: 99%